ISLAMIC LAW IMPLEMENTATION IN ACEH AND CHALLENGES IN THE ERA OF LIBERAL ECONOMICS AND POLITICS - Yusran Hadi, Muhammad; Azahar Kasim (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2024)
Since its declaration on 1 Muharram 1423 H or coinciding with 15 March 2002, Islamic law in Aceh has been under the spotlight. Islamic Sharia, which was revealed by Allah Swt, should be understood as a perfect rule and become rahmatan lil'alamin, instead it gets opposition from some Muslims who are secular and anti-sharia. Some Muslims today, especially leaders and intellectuals in Aceh who claim to be critical but do not have adequate knowledge about Islamic law, dare to reject God's law (sharia). Various negative issues and shubhat are put forward. Among other things, Islamic sharia in Aceh is not in accordance with human nature. In addition, the implementation of sharia in Aceh is said to have been hasty, without careful thought and preparation. This paper attempts to refute these allegations. Whether we realise it or not, negative accusations against the implementation of Islamic sharia in Aceh not only destroy Islamic sharia itself, but also go against the law of God (Allah Swt) and human nature. The accusation that Islamic law in Aceh is incompatible with human nature is a fallacy. Islamic Sharia in Aceh, wherever and whenever, is in accordance with human nature. With Islamic law, human beings discover their nature as servants of Allah and caliphs on earth. Therefore, Islamic law was revealed to guide and protect this human nature so that it does not deviate and is not tyrannised. In addition, this paper also refutes the accusation that Islamic sharia in Aceh was implemented in a hurry. In fact, Islamic sharia in Aceh has been implemented since ancient times, the time of the kingdom of Aceh. However, the implementation of sharia at this time was carried out in stages. That is why, in the beginning, its scope was only limited to certain areas. For example, in criminal law only applies to jarimah khamar, gambling and khalwat / adultery with ta'zir punishment. The next stage is the application of hudud punishment in the case of jarimah hudud. This is the concept of tadarruj that characterises Islamic law itself.